Socio-Cultural Impressions in the Interpretation of Inheritance Verses in Surah An-Nisa: Perspectives from Tafsir Al-Qur’an and Tafsir Al-Qur’an Al-Karim - Parida Ulva Dalimunte; Muhammad Taufiq; Sukma Dewita; Siti Fauziah Ningsih (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
The interpretation of the inheritance verses in Surah An-Nisa cannot be separated from the social and cultural context surrounding the interpreters. This study aims to uncover the socio-cultural impressions in the interpretation of the inheritance verses by three Indonesian exegetes: Zainuddin Hamidy, Fachruddin HS, and Mahmud Yunus. All three lived during the period of the development of modern Islam in Indonesia, marked by efforts to rationalize Islamic teachings and adapt to societal dynamics. The analysis was conducted through a qualitative-descriptive approach using the content analysis method of their exegetes, particularly their interpretations of the inheritance verses in Surah An-Nisa. This study highlights how social conditions, customs, and Islamic legal discourse in Indonesia during their time influenced their interpretation of the principles of justice, gender equality, and inheritance distribution. The results show that the three exegetes provide nuanced interpretations that demonstrate an awareness of the socio-cultural context. Overall, their interpretations reflect an effort to balance sharia norms and social reality, thus enriching the treasury of Indonesian interpretations that are moderate and responsive to changing times.